Empirical DSGE model evaluation with interest rate expectations measures and preferences over safe assets - Gregory De Walque; Thomas Lejeune; Ansgar Rannenberg (National Bank of Belgium, 2023)
We estimate a DSGE model with Preferences Over Safe Assets (POSA) on Euro Area macroeconomic data and interest rate expectations measures. The model with POSA has much better empirical fit than the otherwise identical model without, especially once interest rate expectations are added to the data set. Including measures interest rate expectations strongly improves the model forecast of GDP and its components, with the best forecast delivered by the POSA model. Finally, with POSA, ECB forward guidance increased GDP and inflation by 1.9 % and 0.1 percentage points by 2019Q4, respectively, much less than without POSA.
Keywords: E37; E43; E47; E52; 330; DSGE estimation with interest rate expectations in the data set; forecasting; forward guidance; preferences over safe assets